Diastolic ventricular function in persistent pulmonary hypertension of the newborn - Le Duc, Kévin; Rakza, Thameur; Baudelet, Jean Benoit; Boukhris, Mohamed Riadh; Mur, Sébastien; Houeijeh, Ali; Storme, Laurent (Frontiers in Pediatrics, 2023)
Background: Persistent pulmonary hypertension of the newborn (PPHN) is usually considered a consequence of impaired pulmonary circulation. However, little is known regarding the role of cardiac dysfunction in PPHN. In this study, we hypothesized that the tolerance for pulmonary hypertension in newborn infants depends on the biventricular function. The aim of this study is to evaluate biventricular cardiac performance by using Tissue Doppler Imaging (TDI) in an healthy newborn infants with asymptomatic pulmonary hypertension and in newborn infants with PPHN. Methods: Right and left cardiac function were investigated using conventional imaging and TDI in 10 newborn infants with PPHN (“PPHN”) and 10 asymptomatic healthy newborn infants (“asymptomatic PH”). Results: Systolic pulmonary artery pressure (PAP) as assessed by TDI and the mean systolic velocity of the right ventricular (RV) free wall were similar in both groups. The isovolumic relaxation time of the right ventricle at the tricuspid annulus was significantly longer in the “PPHN” than in the “asymptomatic PH” group (53 ± 14 ms vs. 14 ± 4 ms, respectively; p ˂ 0.05). Left ventricular (LV) function was normal in both groups with a systolic velocity (S’LV) at the LV free wall groups (6 ± 0.5 cm/s vs 8.3 ± 5.7 cm/s, p > 0.05). Conclusion: The present results suggest that high PAP with or without respiratory failure is not associated with altered right systolic ventricular function and does not affect LV function in newborn infants. PPHN is characterized by a marked right diastolic ventricular dysfunction. These data suggest that the hypoxic respiratory failure in PPHN results, at least in part, from diastolic RV dysfunction and right to left shunting across the foramen ovale. We propose that the severity of the respiratory failure is more related to the RV diastolic dysfunction than the pulmonary artery pressure.